2020
DOI: 10.1016/j.hjc.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in renal transplant recipients: an angiographic study

Abstract: In this angiographic study, CAD was less severe in RT than in patients on long-term dialysis despite a longer duration of ESRD. Coronary artery calcification was highly prevalent after renal transplantation. PCI in RT had a high rate of angiographic success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
11
2
Order By: Relevance
“…The prevalence of TVD in these groups of patients has been variable, reported as high as 76%. 18,19 In our study, type B2 (46.2%) was the most common coronary lesion identified. In contrast, an earlier study showed that type C (66.9%) was the most common lesion identified in CKD patients under hemodialysis and that the low eGFR was observed to be a stronger marker of severity and complexity of angiographic lesions in CAD.…”
Section: Discussionmentioning
confidence: 49%
“…The prevalence of TVD in these groups of patients has been variable, reported as high as 76%. 18,19 In our study, type B2 (46.2%) was the most common coronary lesion identified. In contrast, an earlier study showed that type C (66.9%) was the most common lesion identified in CKD patients under hemodialysis and that the low eGFR was observed to be a stronger marker of severity and complexity of angiographic lesions in CAD.…”
Section: Discussionmentioning
confidence: 49%
“…The incidence of CAD among renal transplant (RT) patients is higher than in the general population, ranging from 5–8%, with a cumulative incidence of 1.5% per year [ 7 ]. A recent study highlighted that one significantly calcified lesion was present in 75.7% of patients with RT vs. 15.8% of control patients on patients referred for coronary angiography [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have compared kidney transplantation with patients on dialysis awaiting a transplant, which is already a high-risk population [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both incidence and severity of coronary artery disease are more pronounced in patients suffering from chronic kidney disease (CKD) [1][2][3]. KTR often experienced long-term renal replacement therapy (RRT) while awaiting kidney transplantation with a known adverse impact on atherosclerotic burden and a high coincidence of cardiovascular risk factors such as diabetes or hypertension [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…KTR often experienced long-term renal replacement therapy (RRT) while awaiting kidney transplantation with a known adverse impact on atherosclerotic burden and a high coincidence of cardiovascular risk factors such as diabetes or hypertension [1,4,5]. Even after successful transplantation, cardiovascular disease is highly prevalent in this population and the most frequent cause of death in KTR [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%